The effects of customised food advergames on children’s affective, cognitive, and conative responses - Chapman, Shelly (Cranfield University, 2017)
The practice of promoting food to children via advergames is a highly topical issue which attracts much concern due to the low nutritional value of the promoted foods. This thesis examines the effects of customised food advergames on children’s affective, cognitive and conative responses. It also investigates the role persuasion knowledge and prior brand usage have in children’s interaction with advergames. In particular, whether children’s persuasion knowledge acts as a barrier to those responses. This research is situated within the domains of marketing communications, consumer behaviour and consumer socialisation. It adopts an affect transfer theory, the Dual Mediation Hypothesis (DMH), to explain the transfer of affect from an advergame to children’s responses. Three versions of the same advergame were designed for the purpose of this thesis with different levels of customisation (i.e. control, low and high experimental conditions). An experiment among younger (5-7 year olds) and older (11¬12 year olds) children reveals that customisation in advergames has a detrimental effect on children’s affective, cognitive and conative responses. It was the control condition, without customisation options, that rendered a positive impact on brand attitudes and preferences relative to the other two experimental conditions. Persuasion knowledge does not influence children’s affective, cognitive or conative responses. This implies that children’s understanding of the persuasive intent of an advergame does not act as a barrier against its effects. Age had a significant role on children’s attitudes towards the advergame, but not on their other responses to it. Finally, prior brand usage has a positive impact on children’s responses apart from on advergame attitudes. This thesis has implications to policy and practice. It is evident that children from two distinct age and cognitive developmental groups cannot protect themselves from advergames’ effects. Therefore, regulators should broaden the scope of concern to older and younger children alike.
Keywords: Brand preferences; consumer responses; purchase requests; persuasion knowledge; prior brand usage